HIV and Alcohol Synergistically Disrupt Lysosomal Function in Hepatocytes, Driving Extracellular Vesicle Release and Liver Injury - New-Aaron, Moses; Thomes, Paul G.; Dagur, Raghubendra Singh; Kusum, Kharbanda K.; Poluektova, Larisa Y.; Osna, Natalia A. (Disease and Health: Research Developments Vol. 10, 2025)
Although the etiologies of hepatic complications among people living with HIV who consume alcohol are multifactorial, alcohol remains a relatively understudied contributor to the progression of HIV-related liver injury. Here, we investigated whether metabolically derived acetaldehyde impairs lysosomes and releases exosomes to enhance HIV-induced hepatotoxicity. Cytochrome P450 2E1 (CYP2E1)-expressing Huh 7.5 (also known as RLW) cells were exposed to an acetaldehyde-generating system (AGS) for 24 h. We then infected (or not) the cells with HIV-1ADA, then exposed them again to AGS for another 48 h. Lysosome damage was assessed by galectin 3/LAMP1 co-localisation and cathepsin leakage. Additionally, we measured the co-localisation of DRAM 1 and Bax in lysosomes, indicating the contribution of HIV-AGS-triggered lysosomal damage to apoptosis induction in hepatocytes. Expression of lysosome biogenesis–transcription factor, TFEB, was measured by its protein levels and in situ immunofluorescence. Exposure of cells to AGS + HIV caused the greatest amount of lysosome leakage and impaired lysosomal biogenesis, leading to intrinsic apoptosis. Furthermore, AGS exposure impaired the microtubule-dependent translocation of TFEB from the cytosol to the nucleus. This appeared to result from the acetylation of \(α\)-tubulin. Moreover, ZKSCAN3, a repressor of lysosome gene activation by TFEB, was amplified by AGS. Both these changes contributed to AGS-elicited disruption of lysosome biogenesis and promoted exosome release from hepatocytes. These results demonstrate that acetaldehyde impairs lysosomal integrity and repair, promotes exosome release, and exacerbates HIV-induced hepatotoxicity, offering mechanistic insight into alcohol’s role as a co-factor in liver damage among people with HIV.